O fantástico e o maravilhoso na obra Momo e o senhor do tempo, de Michele Ende - Palaoro, Michele Cristina (2019)
The building of the studies about the fantastic narrative and the wonderful genre in the German literary work Momo (1973), is justified by relating the essential features from the fantastic genre, whose universe finds itself within the ambiguous line between the reason and the incongruity, half way to supernatural and, on the other hand, trace it along the wonderful genre – the naturalized supernaturalism. For it, Tzvetan Todorov (2013, 2017), Furtado (1980), Cunha (2017), García (2007, 2009) and Camarani (2014) debate, in this search about the fantastic. Regards to what traces the genre, the theoretical bases is compound, again, by Todorov (2013, 2017) , also Freud (2001, 2019), Bettelheim (2017) and Corso (2006), regards to the aspects of the child unconscious; and Held (1980), regards to the childish imaginary. The aim of this search is to discuss the concepts of fantastic and wonderful associated to Michael Ende’s work, both theories effectively talk to the reader, leaving the reader simultaneous caught between the ambiguity of the events and their explanation. The results have shown which of the German theories is reticent and ascends to the way where both genres must spread throughout the analysis of the literary work.